Income Responses to Tax Changes - Evidence from the Norwegian Tax Reform - Thor O. Thoresen; Karl Ove Aarbu (Statistics Norway, Research Department, 1999)
Several studies, conducted on U.S. data, have found rather strong income responses to changes in marginal tax rates, when treating tax reforms as "natural experiments" and applying the differences-of-differences estimator on individual income data. The Norwegian tax reform of 1992 implied substantial increases in the net-of-tax rate (1 minus the change in the marginal tax rate) for high-income earners, and this paper provides measures of the elasticity of taxable income with respect to these tax rate changes. The natural experiment assumption of the differences-of-differences approach is discussed. Since the tax reform implied other tax changes and both demographic variables and shifting macroeconomic conditions might impact on income growth, we include other explanatory variables in addition to the net-of-tax rate changes. When including other explanatory variables, tax elasticity estimates are affected, but only modestly. Our estimates of the elasticity of taxable income due to changes in the marginal net-of-tax rate range from about -0.20 to about 0.14.
Keywords: C23; H2; H31; 330; Tax reform; Taxable income elasticity; Differences-of-differences estimator; Natural experiment.